Photocatalyst as well as preparation method and application thereof
By doping single metal atoms in CdS quantum dots and regulating their electron interaction with semiconductor carriers, the problem of insufficient performance of SACs in photoreforming of plastic waste is solved, and efficient photocatalytic and hydrogen evolution performance is achieved.
Patent Information
- Application Number
- CN202510169520.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
How to accurately control the electron interaction between metal single atoms (SACs) and semiconductor carriers to improve the catalytic performance and overall stability of SACs, especially during the photoreforming process of plastic waste.
By doping metal single atoms in CdS quantum dots, using sulfur vacancy to provide anchor positioning points for metal single atoms, regulating the energy band structure of the catalyst, promoting photogenerated electron transfer and carrier separation, thereby improving catalytic efficiency.
The excellent performance of photocatalysts in the conversion and hydrogen evolution process of photocatalytic plastics, improve the stability and atomic utilization rate of the catalyst, and are suitable for large-scale applications.
Smart Images

Figure CN119771446A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalysts and relates to a photocatalyst and a preparation method and application thereof. Background Art
[0002] Currently, there are about 7.4 billion tons of plastic on the planet, and this is expected to increase to 40 billion tons by 2050. In addition, due to the lack of sustainable recycling technology, less than 10% of plastics are recycled worldwide, and more than 70% of waste plastics accumulate in landfills and oceans, posing a huge threat to the global ecosystem. Polyethylene terephthalate (PET) is one of the most common consumer plastics used in the manufacture of disposable plastic bottles and clothing fibers, so it is necessary to develop a gentler and more efficient route for the recycling or upgrading of waste plastics.
[0003] Photoreduction technology is a gentle and sustainable way to recycle and upgrade waste plastics, which can not only reduce waste but also generate valuable products. In the photoreforming system, semiconductor photocatalysts generate electrons and holes under light irradiation. Electrons in the conduction band (CB) photoreduced water into green fuel H2, while holes in the valence band (VB) photooxidatively depolymerized plastics to generate high value-added chemicals.
[0004] In recent years, people have explored a variety of catalysts for PET photoreforming. Compared with ordinary photocatalysts, single-atom catalysts (SACs) have shown certain advantages in the field of catalysis due to their high utilization of active centers and atomic efficiency, and they are more cost-effective and less polluting. For example, CN118949990A discloses a titanium dioxide nanosheet loaded with cobalt single atoms and its application in activating peroxymonosulfate to degrade organic pollutants. The catalyst uses cobalt single atoms as catalytic sites, can efficiently activate peroxymonosulfate to produce strongly oxidizing hydroxyl radicals, achieve efficient oxidative degradation of new antibiotic pollutants, and can maintain excellent catalytic performance in multiple degradation cycles, with good practical application prospects.
[0005] However, there are few studies on the application of SACs in plastic waste, and its application is not yet widespread, but the prospects are broad. Therefore, how to precisely control the electronic interaction between metal single atoms (SACs) and semiconductor supports, namely the electronic metal-support interaction (EMSI), so as to improve the catalytic performance and overall stability of SACs, is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a photocatalyst and a preparation method and application thereof. The present invention dopes metal single atoms into CdS quantum dots as photocatalysts. On the one hand, CdS quantum dots can provide a larger specific surface area and more reactive active sites. On the other hand, the doping of metal single atoms promotes electron transfer in the catalyst. The two act synergistically, so that the catalyst exhibits excellent hydrogen evolution and photocatalytic plastic conversion performance. In addition, the preparation method provided by the present invention is simple and suitable for large-scale application.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a photocatalyst, the photocatalyst comprising CdS quantum dots and metal single atoms doped in the CdS quantum dots;
[0009] The metal single atom includes any one of a transition metal, a rare earth metal or Bi, and the rare earth metal includes Sm or Ce.
[0010] In the present invention, by doping metal single atoms into CdS quantum dots as photocatalysts, on the one hand, sulfur vacancies can provide anchoring points for a large number of metal single atoms, so that the metal single atoms are evenly distributed on the CdS quantum dots; on the other hand, the doping of metal single atoms can introduce impurity energy levels and regulate the energy band structure of the catalyst, thereby promoting the transfer of photogenerated electrons, inhibiting the recombination of carriers, and further accelerating the transfer of photogenerated carriers to the interface to participate in the reaction; at the same time, the structure of the metal single atom doped CdS quantum dots greatly improves the atomic utilization rate and the specific surface area of the catalyst, which is conducive to providing more reaction active sites, thereby improving the catalytic efficiency.
[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0012] Preferably, the metal single atom includes Sm or Bi.
[0013] In the present invention, by selecting Sm or Bi as the metal doping element, since the electron cloud distribution and energy level structure of the Sm element are unique and the chemical properties are stable, it is more conducive to regulating the transmission and separation process of photogenerated carriers, thereby improving the photocatalytic efficiency and stability of the catalyst; and the Bi element has a variety of oxidation states. During the photocatalytic process, it can quickly convert between different oxidation states, effectively participate in the redox reaction, and produce more active species with strong oxidizing properties, thereby more quickly attacking the plastic molecular chain, causing it to break and degrade.
[0014] Preferably, the transition metal includes any one of Ni, Mo or Nb.
[0015] Preferably, when the metal single atom includes a transition metal or a rare earth metal, the mass ratio of the sum of the masses of the CdS quantum dots and the sulfur in the sulfur source to the mass of the metal single atom is 100:(0.01-3), for example, 100:0.01, 100:0.1, 100:0.5, 100:1, 100:1.5, 100:2, 100:2.5 or 100:35, 100, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] Preferably, when the metal single atom includes Bi, the mass ratio of the sum of the masses of the CdS quantum dots and the sulfur in the sulfur source to the metal single atom is 100:(0.03-1.5), for example, 100:0.03, 100:0.05, 100:0.08, 100:0.1, 100:0.2, 100:0.5, 100:0.8, 100:1, 100:1.2 or 100:1.5, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In the present invention, the performance of the catalyst can be adjusted by regulating the doping amount of the metal single atom; when the metal single atom includes a transition metal or a rare earth metal, by controlling the mass ratio of the sum of the mass of the CdS quantum dots and the sulfur in the sulfur source to the metal single atom within the range of 100:(0.01-3), it is more conducive to the uniform doping of the metal single atom in the CdS quantum dots, and the activity and stability of the catalyst can be better taken into account; and when the metal single atom includes Bi, due to the unique properties of Bi, the mass ratio of the sum of the mass of the CdS quantum dots and the sulfur in the sulfur source to the metal single atom is controlled within the range of 100:(0.03-1.5), which will achieve a better catalytic effect.
[0018] Preferably, the average particle size of the CdS quantum dots is 2nm to 3nm, for example 2nm, 2.1nm, 2.2nm, 2.3nm, 2.4nm, 2.5nm, 2.6nm, 2.7nm, 2.8nm, 2.9nm or 3nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the structure of the CdS quantum dots includes a cubic zinc blende structure.
[0020] In a second aspect, the present invention provides a method for preparing the photocatalyst as described in the first aspect, the preparation method comprising:
[0021] (1) first mixing a cadmium source, a doping metal source solution, a thiol compound and a solvent, and adjusting the pH to ≥ 10 using a pH adjuster to obtain a Cd precursor solution;
[0022] (2) performing a second mixing of the Cd precursor solution and a sulfur source, and reacting the mixture under heating conditions to obtain the photocatalyst;
[0023] The doping metal source in the doping metal source solution includes any one of a transition metal source, a rare earth metal source or a Bi source, and the rare earth metal source includes a Sm source or a Ce source.
[0024] In the present invention, the metal single atom-doped CdS quantum dot photocatalyst can be prepared by simply mixing and heating the raw materials at room temperature and pressure. No noble metal co-catalyst and toxic organic coating agent need to be added during the preparation process, and no expensive equipment needs to be used. The preparation cost is low and pollution-free, which is conducive to industrial production. In addition, it should be particularly noted that in step (1), controlling the pH to be ≥10 is more conducive to the uniform dispersion of the doped metal and the stability of the CdS quantum dots.
[0025] The pH value adjusted by using a pH adjuster to ≥ 10 may be, for example, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5 or 14, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the transition metal source includes any one of a Ni source, a Mo source or a Nb source.
[0027] Preferably, the doping metal source includes a Sm source or a Bi source.
[0028] Preferably, the concentration of the doping metal source solution is 0.005mol / L to 0.02mol / L, for example, 0.005mol / L, 0.007mol / L, 0.01mol / L, 0.012mol / L, 0.014mol / L, 0.016mol / L, 0.018mol / L or 0.02mol / L, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, when the doping metal source includes a transition metal source or a rare earth metal source, the mass ratio of the sum of the mass of cadmium in the cadmium source and the mass of sulfur in the sulfur source to the doping metal in the doping metal source is 100:(0.01~3), for example, 100:0.01, 100:0.1, 100:0.5, 100:1, 100:1.5, 100:2, 100:2.5 or 100:3, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, when the doping metal source includes a Bi source, the mass ratio of the sum of the masses of cadmium in the cadmium source and sulfur in the sulfur source to the mass of the doping metal in the doping metal source is 100:(0.03-1.5), for example, 100:0.03, 100:0.05, 100:0.08, 100:0.1, 100:0.2, 100:0.5, 100:0.8, 100:1, 100:1.2 or 100:1.5, etc., but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0031] In the present invention, by regulating the mass ratio of the sum of the masses of cadmium in the cadmium source and sulfur in the sulfur source to the mass ratio of the doped metal in the doped metal source, a photocatalyst with different metal single atom doping amounts can be obtained.
[0032] Preferably, the molar ratio of the cadmium source and the thiol compound is (50-70):1, for example 50:1, 52:1, 55:1, 57:1, 60:1, 62:1, 65:1, 67:1 or 70:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the pH adjuster comprises NaOH solution.
[0034] Preferably, the mass fraction of NaOH in the NaOH solution is 20% to 40%, for example 20%, 23%, 25%, 28%, 30%, 32%, 35%, 37% or 40%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the first mixing is performed under stirring.
[0036] Preferably, the sulfur source comprises sodium sulfide.
[0037] Preferably, the molar ratio of the cadmium source to the sulfur source is (0.9-1.1):(0.9-1.1), for example 0.9:0.9, 0.9:1.0, 0.9:1.1, 1.0:0.9, 1.0:1.1, 1.1:0.9 or 1.1:1.0, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] The present invention can optimize the morphology, electronic structure and doping uniformity of CdS quantum dots by precisely regulating the molar ratio of the sum of the mass of cadmium in the cadmium source and sulfur in the sulfur source to the doped metal in the doped metal source, the molar ratio of the cadmium source and the thiol compound, and the molar ratio of the cadmium source and the sulfur source, thereby improving the photocatalytic performance and stability of the catalyst. Among them, the preferred doped metal ratio is more conducive to forming a stable single-atom active site and enhancing the separation efficiency of photogenerated carriers; the preferred cadmium source and thiol compound ratio can regulate the size and dispersibility of CdS quantum dots, which is more conducive to reducing surface defects and improving catalytic stability; the preferred cadmium source and sulfur source ratio is more conducive to promoting uniform nucleation of CdS, reducing structural defects, and improving light absorption capacity and carrier migration efficiency. Through multiple ratio optimization, the catalyst can show higher activity and long-term stability in the process of photocatalytic reforming of plastics.
[0039] Preferably, step (2) is carried out in an inert gas atmosphere.
[0040] Preferably, the reaction in step (2) is carried out under stirring.
[0041] Preferably, the reaction temperature in step (2) is 115°C to 125°C, for example, 115°C, 117°C, 119°C, 120°C, 122°C or 125°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, the reaction time of step (2) is 30 min to 75 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min or 75 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In the present invention, the structure and particle size of CdS quantum dots can be adjusted by regulating the temperature and / or time of the reaction. By controlling the reaction temperature within the range of 115°C to 125°C and the reaction time within the range of 30min to 75min, on the one hand, it is more conducive to obtaining CdS quantum dots with appropriate crystal defects and smaller particle size; on the other hand, it is more conducive to uniformly doping metal single atoms into CdS quantum dots. The two act synergistically, so that the catalyst exhibits more excellent photocatalytic performance.
[0044] Preferably, the product after the reaction in step (2) is washed and dried in sequence.
[0045] Preferably, the washing method comprises washing multiple times in a mixed solution of secondary water and ethanol.
[0046] Preferably, the drying temperature is 70°C to 90°C, for example 70°C, 73°C, 76°C, 80°C, 83°C, 85°C, 88°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the drying time is 5 h to 7 h, for example, 5 h, 5.3 h, 5.6 h, 6 h, 6.3 h, 6.6 h or 7 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0049] (1) preparing a doping metal source solution with a concentration of 0.005 mol / L to 0.02 mol / L, and mixing the prepared doping metal source solution, the cadmium source, the thiol compound and the solvent in a molar ratio of 50 to 70:1 under stirring, and then adjusting the pH to ≥ 10 using a NaOH solution with a NaOH mass fraction of 20% to 40% to obtain a Cd precursor solution;
[0050] (2) in an inert gas atmosphere and under stirring conditions, the Cd precursor solution and the sulfur source are mixed for a second time according to a molar ratio of cadmium source to sulfur source (0.9-1.1):(0.9-1.1), reacted at 115° C. to 125° C. for 30 min to 75 min, the reaction product is washed multiple times in a mixed solution of secondary water and ethanol, and dried at 70° C. to 90° C. for 5 h to 7 h to obtain the photocatalyst;
[0051] The doping metal source includes a Sm source or a Bi source;
[0052] When the doping metal source includes an Sm source, the mass ratio of the sum of the mass of cadmium in the cadmium source and the sulfur in the sulfur source to the doping metal in the doping metal source is 100:(0.01~3); when the doping metal source includes a Bi source, the mass ratio of the sum of the mass of cadmium in the cadmium source and the sulfur in the sulfur source to the doping metal in the doping metal source is 100:(0.03~1.5).
[0053] In a third aspect, the present invention further provides an application of the photocatalyst as described in the first aspect in the degradation of plastic waste.
[0054] The catalyst provided by the present invention is applied in the field of plastic waste degradation. Without using a co-catalyst and under 365nm light excitation conditions, the photocatalytic hydrogen evolution rate can be as high as 6047μmol / g / h, which is much higher than the hydrogen evolution rate of the CdS quantum dot catalyst without metal single atom doping, and is suitable for promotion and application.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] (1) The photocatalyst provided by the present invention is a zero-dimensional material, which is more conducive to the directional transmission and migration of photogenerated carriers. The catalyst has a large specific surface area, can expose more active sites, and has excellent photoreforming performance and hydrogen evolution activity for plastics.
[0057] (2) The present invention uses defective CdS quantum dots as precursors. The defects can promote the absorption of visible light and inhibit the recombination of photogenerated carriers. On the other hand, they can serve as anchoring points for single atoms, thereby regulating the stability of the catalyst and preventing agglomeration.
[0058] (3) The preparation method of the photocatalyst provided by the present invention can be carried out at room temperature and pressure, has low requirements on equipment, does not require the addition of precious metal co-catalysts and toxic organic coating agents, has high atomic utilization and low price, and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 TEM images of the photocatalysts provided for Example 1 and Comparative Example 1 and the corresponding selected area electron diffraction images.
[0060] Figure 2 Particle size distribution diagram of the photocatalyst provided for Example 1 and Comparative Example 1.
[0061] Figure 3 XRD patterns of the photocatalysts provided for Example 1 and Comparative Example 1.
[0062] Figure 4 Raman graphs of the photocatalysts provided for Example 1 and Comparative Example 1.
[0063] Figure 5 IR graphs of the photocatalysts provided for Example 1 and Comparative Example 1.
[0064] Figure 6 The adsorption-desorption isotherm curves of the photocatalysts provided for Example 1 and Comparative Example 1.
[0065] Figure 7 The pore size distribution diagram of the photocatalyst provided for Example 1 and Comparative Example 1.
[0066] Figure 8 XPS spectra of the photocatalysts provided for Example 1 and Comparative Example 1.
[0067] Fig. 9 XPS spectra of the S element 2p orbital of the photocatalysts provided in Example 1 and Comparative Example 1.
[0068] Fig.10XPS spectra of the Cd element 3d orbital of the photocatalyst provided in Example 1 and Comparative Example 1.
[0069] Fig.11 UV-visible diffuse reflectance images of the photocatalysts provided for Example 1 and Comparative Example 1.
[0070] Fig.12 Tauc plots of the photocatalysts provided for Example 1 and Comparative Example 1.
[0071] Fig.13 MS graphs of the photocatalysts provided for Example 1 and Comparative Example 1.
[0072] Fig.14 XPS valence band spectra of the photocatalysts provided in Example 1 and Comparative Example 1.
[0073] Fig.15 The energy band structure diagram of the photocatalyst provided for Example 1 and Comparative Example 1.
[0074] Fig.16 PL spectra of the photocatalysts provided for Example 1 and Comparative Example 1.
[0075] Fig.17 Fluorescence lifetime decay curves of the photocatalysts provided for Example 1 and Comparative Example 1 (excited at λ=375nm).
[0076] Fig.18 It diagram of the photocatalyst provided for Example 1 and Comparative Example 1.
[0077] Fig.19 EIS graphs of the photocatalysts provided for Example 1 and Comparative Example 1.
[0078] Fig. 20 TEM images of the photocatalysts provided for Example 2 and Comparative Example 1 and the corresponding selected area electron diffraction images.
[0079] Fig.21 Particle size distribution diagram of the photocatalyst provided for Example 2 and Comparative Example 1.
[0080] Fig. 22 XRD patterns of the photocatalysts provided for Example 2 and Comparative Example 1.
[0081] Fig.23 3 is the Raman graph of the photocatalyst provided in Example 2 and Comparative Example 1.
[0082] Fig.24 IR graphs of the photocatalysts provided for Example 2 and Comparative Example 1.
[0083] Fig.25The adsorption-desorption isotherms of the photocatalysts provided for Example 2 and Comparative Example 1.
[0084] Fig.26 The pore size distribution diagram of the photocatalyst provided for Example 2 and Comparative Example 1.
[0085] Fig. 27 XPS spectra of the photocatalysts provided for Example 2 and Comparative Example 1.
[0086] Fig.28 XPS spectra of the Cd element 3d orbital of the photocatalyst provided for Example 2 and Comparative Example 1.
[0087] Fig.29 XPS spectra of the S element 2p orbital of the photocatalysts provided in Example 2 and Comparative Example 1.
[0088] Fig.30 UV-visible diffuse reflectance images of the photocatalysts provided for Example 2 and Comparative Example 1.
[0089] Fig.31 Tauc plots of the photocatalysts provided for Example 2 and Comparative Example 1.
[0090] Fig.32 MS graphs of the photocatalysts provided for Example 2 and Comparative Example 1.
[0091] Fig.33 XPS valence band spectra of the photocatalysts provided for Example 2 and Comparative Example 1.
[0092] Fig.34 The energy band structure diagram of the photocatalyst provided for Example 2 and Comparative Example 1.
[0093] Fig.35 PL spectra of the photocatalysts provided in Example 2 and Comparative Example 1.
[0094] Fig.36 Fluorescence lifetime decay curves of the photocatalysts provided for Example 2 and Comparative Example 1 (excited at λ=375 nm).
[0095] Fig.37 It diagram of the photocatalyst provided for Example 2 and Comparative Example 1.
[0096] Fig.38 EIS graphs of the photocatalysts provided for Example 2 and Comparative Example 1. DETAILED DESCRIPTION
[0097] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0098] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0099] Example 1
[0100] This embodiment provides a photocatalyst, including CdS quantum dots and Bi single atoms doped in the CdS quantum dots, wherein the theoretical doping amount of Bi is 0.1 wt%. The preparation method is as follows:
[0101] (1) According to the molar ratio of cadmium chloride to 3-mercaptopropionic acid of 60:1, 0.182 g of cadmium chloride and 0.00176 g of 3-mercaptopropionic acid were weighed and dissolved in deionized water, 60 μL of 0.01 mol / L bismuth nitrate aqueous solution was added, and after stirring and fully dissolving, a cadmium chloride precursor solution was obtained. A NaOH aqueous solution with a mass fraction of 30% was added dropwise to the solution and the pH of the solution was detected until the pH of the solution was ≥10, thereby obtaining a Cd precursor solution.
[0102] (2) Ar is continuously introduced into the Cd precursor solution, and sodium sulfide is added to the Cd precursor solution at a molar ratio of cadmium chloride to sodium sulfide of 1:1 under stirring to obtain a mixed solution. The mixed solution is heated to 120°C, and reacted at 120°C for 1 hour, then cooled in water, filtered, and washed with water and ethanol in a volume ratio of 1:1 for 3 times by centrifugation. The washed filtered product is dried at 80°C for 6 hours to obtain a Bi single atom-doped CdS quantum dot photocatalyst.
[0103] Example 2
[0104] This embodiment provides a photocatalyst, including CdS quantum dots and Sm single atoms doped in the CdS quantum dots, wherein the theoretical doping amount of Sm is 0.02 wt%. The preparation method is as follows:
[0105] (1) According to the molar ratio of cadmium chloride to 3-mercaptopropionic acid of 60:1, 0.182 g of cadmium chloride and 0.00176 g of 3-mercaptopropionic acid were weighed and dissolved in deionized water, 20 μL of 0.01 mol / L samarium chloride aqueous solution was added, and after stirring and fully dissolved, a cadmium chloride precursor solution was obtained. A NaOH aqueous solution with a mass fraction of 30% was added dropwise to the solution and the pH of the solution was detected until the pH of the solution was ≥10, thereby obtaining a Cd precursor solution.
[0106] (2) Ar is continuously introduced into the Cd precursor solution, and sodium sulfide is added to the Cd precursor solution at a molar ratio of cadmium chloride to sodium sulfide of 1:1 under stirring to obtain a mixed solution. The mixed solution is heated to 120°C, and reacted at 120°C for 1 hour, then cooled in water, filtered, and washed with water and ethanol in a volume ratio of 1:1 for 3 times by centrifugation. The washed filtered product is dried at 80°C for 6 hours to obtain a Sm single atom-doped CdS quantum dot photocatalyst.
[0107] Example 3
[0108] This embodiment provides a photocatalyst, including CdS quantum dots and Mo single atoms doped in the CdS quantum dots, wherein the theoretical doping amount of Mo is 0.05 wt%. The preparation method is as follows:
[0109] (1) According to the molar ratio of cadmium chloride to 3-mercaptopropionic acid of 60:1, 0.182 g of cadmium chloride and 0.00176 g of 3-mercaptopropionic acid were weighed and dissolved in deionized water, 60 μL of 0.01 mol / L molybdenum chloride aqueous solution was added, and after stirring and fully dissolving, a cadmium chloride precursor solution was obtained. A NaOH aqueous solution with a mass fraction of 30% was added dropwise to the solution and the pH of the solution was detected until the pH of the solution was ≥10, thereby obtaining a Cd precursor solution.
[0110] (2) Ar is continuously introduced into the Cd precursor solution, and sodium sulfide is added to the Cd precursor solution at a molar ratio of cadmium chloride to sodium sulfide of 1:1 under stirring to obtain a mixed solution. The mixed solution is heated to 120°C, and reacted at 120°C for 1 hour, then cooled in water, filtered, and washed with water and ethanol in a volume ratio of 1:1 for 3 times by centrifugation. The washed filtered product is dried at 80°C for 6 hours to obtain a Mo single atom-doped CdS quantum dot photocatalyst.
[0111] Example 4
[0112] This embodiment provides a photocatalyst, including CdS quantum dots and Bi single atoms doped in the CdS quantum dots, wherein the theoretical doping amount of Bi is 0.1 wt%. The preparation method is as follows:
[0113] (1) According to the molar ratio of cadmium chloride to 3-mercaptopropionic acid of 50:1, 0.182 g of cadmium chloride and 0.00211 g of 3-mercaptopropionic acid were weighed and dissolved in deionized water, 60 μL of 0.01 mol / L bismuth nitrate aqueous solution was added, and after stirring and fully dissolving, a cadmium chloride precursor solution was obtained. A NaOH aqueous solution with a mass fraction of 20% was added dropwise to the solution and the pH of the solution was detected until the pH of the solution was ≥10, thereby obtaining a Cd precursor solution.
[0114] (2) Ar was continuously introduced into the Cd precursor solution, and sodium sulfide was added to the Cd precursor solution at a molar ratio of cadmium chloride to sodium sulfide of 0.9:1.1 under stirring to obtain a mixed solution. The mixed solution was heated to 115°C, and reacted at 115°C for 75 minutes, then cooled in water, filtered, and washed with water and ethanol in a volume ratio of 1:1 for 3 times by centrifugation. The washed filtered product was dried at 70°C for 7 hours to obtain a Bi single atom-doped CdS quantum dot photocatalyst.
[0115] Example 5
[0116] This embodiment provides a photocatalyst, including CdS quantum dots and Bi single atoms doped in the CdS quantum dots, wherein the theoretical doping amount of Bi is 0.1 wt%. The preparation method is as follows:
[0117] (1) According to the molar ratio of cadmium chloride to 3-mercaptopropionic acid of 70:1, 0.182 g of cadmium chloride and 0.00151 g of 3-mercaptopropionic acid were weighed and dissolved in deionized water, 60 μL of 0.01 mol / L bismuth nitrate aqueous solution was added, and after stirring and fully dissolving, a cadmium chloride precursor solution was obtained. A NaOH aqueous solution with a mass fraction of 20% was added dropwise to the solution and the pH of the solution was detected until the pH of the solution was ≥10, thereby obtaining a Cd precursor solution.
[0118] (2) Ar was continuously introduced into the Cd precursor solution, and sodium sulfide was added to the Cd precursor solution at a molar ratio of cadmium chloride to sodium sulfide of 1.1:0.9 under stirring to obtain a mixed solution. The mixed solution was heated to 125°C, and reacted at 125°C for 30 minutes, then cooled in water, filtered, and washed with water and ethanol in a volume ratio of 1:1 for 3 times by centrifugation. The washed filtered product was dried at 90°C for 5 hours to obtain a Bi single atom-doped CdS quantum dot photocatalyst.
[0119] Example 6
[0120] The difference between this embodiment and embodiment 1 is that in this embodiment, the theoretical doping amount of Bi is 0.03 wt %, and in step (1) of the preparation method, 20 μL of a 0.01 mol / L bismuth nitrate aqueous solution is added.
[0121] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0122] Example 7
[0123] The difference between this embodiment and embodiment 1 is that in this embodiment, the theoretical doping amount of Bi is 0.06 wt %, and in step (1) of the preparation method, 40 μL of a 0.01 mol / L bismuth nitrate aqueous solution is added.
[0124] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0125] Example 8
[0126] The difference between this embodiment and embodiment 1 is that in this embodiment, the theoretical doping amount of Bi is 0.5 wt %, and in step (1) of the preparation method, 300 μL of a 0.01 mol / L bismuth nitrate aqueous solution is added.
[0127] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0128] Example 9
[0129] The difference between this embodiment and embodiment 1 is that in this embodiment, the theoretical doping amount of Bi is 1 wt %, and in step (1) of the preparation method, 600 μL of a 0.01 mol / L bismuth nitrate aqueous solution is added.
[0130] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0131] Example 10
[0132] The difference between this embodiment and embodiment 1 is that in this embodiment, the theoretical doping amount of Bi is 1.5 wt %, and in step (1) of the preparation method, 900 μL of a 0.01 mol / L bismuth nitrate aqueous solution is added.
[0133] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0134] Embodiment 11
[0135] The difference between this embodiment and embodiment 2 is that in this embodiment, the theoretical doping amount of Sm is 0.01 wt %, and in step (1) of the preparation method, 10 μL of a samarium chloride aqueous solution with a concentration of 0.01 mol / L is added.
[0136] The rest of the preparation methods and parameters were consistent with those in Example 2.
[0137] Example 12
[0138] The difference between this embodiment and embodiment 2 is that in this embodiment, the theoretical doping amount of Sm is 0.04 wt %, and in step (1) of the preparation method, 40 μL of a samarium chloride aqueous solution with a concentration of 0.01 mol / L is added.
[0139] The rest of the preparation methods and parameters were consistent with those in Example 2.
[0140] Example 13
[0141] The difference between this embodiment and embodiment 2 is that in this embodiment, the theoretical doping amount of Sm is 0.06 wt %, and in step (1) of the preparation method, 60 μL of a samarium chloride aqueous solution with a concentration of 0.01 mol / L is added.
[0142] The rest of the preparation methods and parameters were consistent with those in Example 2.
[0143] Embodiment 14
[0144] The difference between this embodiment and embodiment 2 is that in this embodiment, the theoretical doping amount of Sm is 0.2 wt %, and in step (1) of the preparation method, 200 μL of a samarium chloride aqueous solution with a concentration of 0.01 mol / L is added.
[0145] The rest of the preparation methods and parameters were consistent with those in Example 2.
[0146] Embodiment 15
[0147] The difference between this embodiment and embodiment 2 is that in this embodiment, the theoretical doping amount of Sm is 1 wt %, and in step (1) of the preparation method, 1000 μL of a samarium chloride aqueous solution with a concentration of 0.01 mol / L is added.
[0148] The rest of the preparation methods and parameters were consistent with those in Example 2.
[0149] Example 16
[0150] The difference between this embodiment and embodiment 2 is that in this embodiment, the theoretical doping amount of Sm is 2 wt %, and in step (1) of the preparation method, 2000 μL of a samarium chloride aqueous solution with a concentration of 0.01 mol / L is added.
[0151] The rest of the preparation methods and parameters were consistent with those in Example 2.
[0152] Embodiment 17
[0153] The difference between this embodiment and embodiment 2 is that in this embodiment, the theoretical doping amount of Sm is 2.5 wt % and in step (1) of the preparation method, 2500 μL of a samarium chloride aqueous solution with a concentration of 0.01 mol / L is added.
[0154] The rest of the preparation methods and parameters are consistent with those in Example 2.
[0155] Embodiment 18
[0156] The difference between this embodiment and embodiment 2 is that in this embodiment, the theoretical doping amount of Sm is 3 wt % and in step (1) of the preparation method, 3000 μL of a samarium chloride aqueous solution with a concentration of 0.01 mol / L is added.
[0157] The rest of the preparation methods and parameters are consistent with those in Example 2.
[0158] Embodiment 19
[0159] The difference between this embodiment and embodiment 1 is that in this embodiment, the photocatalyst includes CdS quantum dots and Ni single atoms doped in the CdS quantum dots, and the theoretical doping amount of Ni is 0.03wt%; in the preparation method step (1), 60μL of a nickel chloride aqueous solution with a concentration of 0.01mol / L is added.
[0160] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0161] Embodiment 20
[0162] The difference between this embodiment and embodiment 1 is that in this embodiment, the photocatalyst includes CdS quantum dots and Nb single atoms doped in the CdS quantum dots, and the theoretical doping amount of Nb is 0.04wt%; in the preparation method step (1), 60μL of 0.01mol / L niobium pentachloride aqueous solution is added.
[0163] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0164] Embodiment 21
[0165] The difference between this embodiment and embodiment 1 is that in this embodiment, the photocatalyst includes CdS quantum dots and Ce single atoms doped in the CdS quantum dots, and the theoretical doping amount of Ce is 0.07wt%; in the preparation method step (1), 60μL of a 0.01mol / L cerium chloride aqueous solution is added.
[0166] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0167] Embodiment 22
[0168] The difference between this embodiment and embodiment 1 is that in step (2) of the preparation method, the Cd precursor solution and the sulfur source are mixed for a second time according to a molar ratio of the cadmium source to the sulfur source of 1:0.8.
[0169] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0170] Embodiment 23
[0171] The difference between this embodiment and embodiment 1 is that in step (1) of the preparation method, the prepared metal source solution, cadmium source, mercapto compound and solvent are first mixed under stirring according to a molar ratio of cadmium chloride to 3-mercaptopropionic acid of 40:1.
[0172] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0173] Embodiment 24
[0174] The difference between this embodiment and embodiment 1 is that in step (2) of the preparation method, the reaction is carried out at 135° C. for 90 minutes.
[0175] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0176] Embodiment 25
[0177] The difference between this embodiment and embodiment 1 is that in step (2) of the preparation method, the reaction is carried out at 105° C. for 20 min.
[0178] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0179] Embodiment 26
[0180] The difference between this embodiment and embodiment 1 is that in this embodiment, the theoretical doping amount of Bi is 2 wt %, and in step (1) of the preparation method, 1200 μL of a 0.01 mol / L bismuth nitrate aqueous solution is added.
[0181] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0182] Embodiment 27
[0183] The difference between this embodiment and embodiment 1 is that in this embodiment, the theoretical doping amount of Bi is 2.5 wt %, and in step (1) of the preparation method, 1500 μL of a 0.01 mol / L bismuth nitrate aqueous solution is added.
[0184] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0185] Embodiment 28
[0186] The difference between this embodiment and embodiment 1 is that in this embodiment, the theoretical doping amount of Bi is 3 wt %, and in step (1) of the preparation method, 1800 μL of a 0.01 mol / L bismuth nitrate aqueous solution is added.
[0187] Comparative Example 1
[0188] The difference between this comparative example and Example 1 is that the photocatalyst includes CdS quantum dots and is not doped with metal single atoms, and in step (1) of the preparation method, no bismuth nitrate aqueous solution is added.
[0189] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0190] Comparative Example 2
[0191] The difference between this comparative example and Example 1 is that in this comparative example, the photocatalyst includes CdS quantum dots and Yb single atoms doped in the CdS quantum dots, and the theoretical doping amount of Yb is 0.08wt%; in the preparation method step (1), 60μL of 0.01mol / L ytterbium nitrate aqueous solution is added.
[0192] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0193] Comparative Example 3
[0194] The difference between this comparative example and Example 1 is that in step (1) of the preparation method, pH is adjusted to 6.
[0195] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0196] Structural characterization
[0197] The photocatalysts prepared in Example 1, Example 2 and Comparative Example 1 were subjected to X-ray photoelectron spectroscopy test (XPS), X-ray diffraction test (XRD), infrared spectroscopy test (IR), model Schottky test (MS), Raman test (Raman), electron paramagnetic resonance test (EPR), particle size distribution test, transmission electron microscopy test (TEM), specific surface area test (BET), UV-visible diffuse reflectance spectroscopy test, photoluminescence spectroscopy test (PL), fluorescence lifetime decay test, electrochemical impedance spectroscopy test (EIS) and photocurrent test, and the results are as follows: Figure 1-Figure 38 As shown; the photocatalysts prepared in Example 1, Example 2 and Comparative Example 1 were subjected to inductively coupled plasma testing (ICP), and the test results are shown in Table 1.
[0198] Table 1
[0199] Serial number Element ratio Actual doping amount of Bi or Sm (wt%) Example 1 Cd:S=1:0.88 0.08 Example 2 Cd:S=1:0.84 0.015 Comparative Example 1 Cd:S=1:0.89 0
[0200] Performance Testing
[0201] The photoreforming hydrogen evolution activity of the photocatalysts prepared in Examples 1-28 and Comparative Examples 1-3 on PET plastic was measured by gas chromatography (GC). The results are shown in Table 2:
[0202] Table 2
[0203]
[0204]
[0205] Depend on Figure 1 It can be seen that the preparation method of the present invention successfully synthesized CdS quantum dots with uniform size. Figure 2 It can be seen that after Bi doping, the particle size of CdS quantum dots increases slightly to about 2.14 nm.
[0206] Depend on Figure 3 It can be seen that the photocatalysts prepared in Example 1 and Comparative Example 1 have strong diffraction peaks at 26.71°, 44.17° and 52.06°, which correspond to the (220), (200), (311) and (111) crystal planes of the CdS cubic sphalerite structure, respectively. Figure 4 As you can see, 302cm -1 and 589cm -1 There are two typical Raman spectral bands of CdS quantum dots, which shows that CdS quantum dots are successfully synthesized and the addition of trace amounts of Bi does not change the crystal structure of CdS. Figure 5 The IR spectrum shown has typical CdS characteristic peaks at 1004 and 658 cm -1 The two peaks are the stretching vibration of Cd-S at 660 cm -1 The characteristic absorption peak at 624 cm -1 A blue shift occurs at the position where Bi-S is present.
[0207] Depend on Figure 6 to Figure 7 It can be seen from the BET diagram that the N2 adsorption-desorption isotherms of the photocatalysts prepared in Example 1 and Comparative Example 1 are both type IV isotherms, and there is an obvious hysteresis phenomenon in the desorption curve, which manifests as an H3 type hysteresis loop; Example 1 shows a higher specific surface area, which indicates that the doping of metal Bi exposes more reaction sites in the catalyst and enhances the photocatalytic activity of the material.
[0208] Figures 8 to 9The full spectra of Example 1 and Comparative Example 1 and the corresponding XPS spectra of the 3d orbital of the Cd element and the 2p orbital of the S element are respectively represented. Compared with those of Comparative Example 1, the peak values of the 3d orbital of the Cd element and the 2p orbital of the S element in Example 1 are that the 3d orbital of the Cd element shifts toward the high binding energy direction, and the 2p orbital of the S element shifts toward the high binding energy direction. These peak shifts indicate that there is charge transfer between CdS and Bi, indicating that a single-atom photocatalyst on metal-doped CdS quantum dots is successfully prepared.
[0209] Depend on Fig.11 It can be seen that the photocatalysts prepared in Example 1 and Comparative Example 1 both exhibit a good red shift phenomenon. Further calculations are made on their band gaps, as shown in FIG. Fig.12 As shown, it can be seen that the band gap of the photocatalyst after loading Bi single atoms becomes significantly smaller, indicating that the photocatalyst prepared by the present invention has a good light absorption range. According to the Tauc equation, the corresponding band gaps are 2.68 eV and 2.76 eV, respectively.
[0210] Depend on Fig.13 It can be seen that the flat band potentials of the photocatalysts prepared in Example 1 and Comparative Example 1 are -0.78 V and -0.67 V, respectively. The conduction band potentials can be calculated to be approximately -0.68 V and -0.57 V (vs. Ag / AgCl, pH = 7). From EVB = ECB + Eg, it can be seen that the corresponding valence bands (VB) are 2.00 V and 2.19 V (vs. NHE, pH = 7), respectively. Fig.14 It can be seen that the corresponding valence bands are 1.91eV and 2.09eV, which are close to the valence band values obtained previously, and the accurate band structures of the four catalysts are further determined, such as Fig.15 Shown is the corresponding band structure diagram.
[0211] Depend on Fig.16 It can be seen that the fluorescence intensity of Comparative Example 1 is higher than that of Example 1, which indicates that the recombination of photogenerated electrons and holes in Example 1 is less than that in Comparative Example 1. Example 1 can effectively improve the recombination of photogenerated electrons and holes, thereby improving the photocatalytic performance. Fig.17 The shorter fluorescence lifetime in the fluorescence lifetime decay curve further indicates that Example 1 can exhibit better photogenerated carrier separation efficiency.
[0212] like Fig.18 As shown in the photocurrent diagram, the photocatalyst obtained in Example 1 has a larger photocurrent than that in Comparative Example 1 and has a higher carrier transfer efficiency. Fig.19 As shown, the charge transfer resistance of the CdS quantum dot photocatalyst doped with metal Bi is reduced, and the transmission efficiency of photogenerated electrons and holes is higher. At the same time, compared with neutral conditions, alkaline conditions can further promote the separation of photogenerated electron-hole pairs.
[0213] Depend on Fig. 20 It can be seen that the preparation method provided by the present invention successfully synthesized CdS quantum dots with uniform size, such as Fig.21 As shown, after Sm doping, the particle size of CdS quantum dots increases slightly to about 2.21 nm.
[0214] like Fig. 22 As shown in Figure 2, strong diffraction peaks appear at 26.71°, 44.17° and 52.06°, corresponding to the (220), (200), (311) and (111) crystal planes of the CdS cubic zinc blende structure, respectively. Fig.23 As shown, at 302cm -1 and 589cm -1 There are two typical Raman spectral bands of CdS quantum dots, which indicates that CdS quantum dots are successfully synthesized and that the addition of Sm does not change the crystal structure of CdS. Fig.24 As shown in the figure, a typical CdS characteristic peak of 1004cm -1 and 658cm -1 The two peaks are the stretching vibration of Cd-S at 787 cm -1 The peak at is the stretching vibration peak of Sm-S, indicating the successful doping of Sm.
[0215] like Figure 25 to Figure 26 As shown in the BET diagram, the N2 adsorption-desorption isotherms all belong to type IV isotherms, and the desorption curve has obvious hysteresis phenomenon, which manifests as an H3 type hysteresis loop; Example 2 shows a higher specific surface area, indicating that after metal Sm doping, the catalyst exposes more reaction sites, thereby enhancing the photocatalytic activity of the material.
[0216] Figure 27 to Figure 29 As shown, they respectively represent the full spectrum of the photocatalyst and the corresponding XPS spectra of the 3d orbital of the Cd element and the 2p orbital of the S element. Compared with the comparative example 1, the peak values of the 3d orbital of the Cd element and the 2p orbital of the S element in Example 2 are that the 3d orbital of the Cd element shifts toward the high binding energy direction, and the 2p orbital of the S element shifts toward the high binding energy direction. These peak shifts indicate that there is charge transfer between CdS and Sm, indicating that this patent successfully prepared a single-atom photocatalyst in which Sm is loaded on CdS quantum dots.
[0217] Depend on Fig.30 It can be seen that the catalysts prepared by the present invention all show a good red shift phenomenon; further calculation of their band gaps shows that Fig.31As shown, the band gap of the photocatalyst after loading Sm single atoms becomes significantly smaller, indicating that the metal-doped CdS quantum dot photocatalyst has a good light absorption range. According to the Tauc equation, the corresponding band gaps are 2.71eV and 2.76eV, respectively.
[0218] like Fig.32 As shown, the flat band potentials of the photocatalysts prepared in Example 2 and Comparative Example 1 are -0.73 V and -0.67 V, respectively. The conduction band potentials can be calculated to be approximately -0.63 V and -0.57 V (vs. Ag / AgCl, pH = 7). From EVB = ECB + Eg, it can be seen that the corresponding valence bands (VB) are 2.08 V and 2.14 V (vs. NHE, pH = 7), respectively. Fig.33 It can be seen that the corresponding valence bands are 2.01eV and 2.32eV, which are close to the valence band values obtained previously, and further determine the accurate band structures of the four catalysts, such as Fig.34 Shown is the corresponding band structure diagram.
[0219] like Fig.35 As shown, the fluorescence intensity of comparative example 1 is higher than that of example 2, indicating that the phenomenon of recombination of photogenerated electrons and holes in example 2 is less than that in comparative example 1, and the doping of metal Sm can effectively improve the recombination of photogenerated electrons and holes, thereby improving the photocatalytic performance. Fig.36 The shorter fluorescence lifetime in the fluorescence lifetime decay curve further indicates that Example 2 can exhibit better photogenerated carrier separation efficiency.
[0220] like Fig.37 As shown in the photocurrent diagram, the metal-doped CdS quantum dots obtained in Example 2 have a larger photocurrent than those in Comparative Example 1, and have a higher carrier transfer efficiency; Fig.38 As shown, the charge transfer resistance of the CdS quantum dot photocatalyst doped with metal Sm is reduced, and the transmission efficiency of photogenerated electrons and holes is higher. At the same time, compared with neutral conditions, alkaline conditions further promote the separation of photogenerated electron-hole pairs.
[0221] It can be seen from Table 1 that by adjusting the molar ratio of cadmium in the cadmium source and the doping metal in the doping metal source during the preparation process, the doping amount of metal single atoms in the photocatalyst can be controlled. In the final product, the actual doping amount of metal single atoms is slightly reduced compared to the theoretical doping amount, but is generally close.
[0222] From the data comparison between Example 1 and Comparative Example 1 in Table 2, it can be seen that the doping of metal single atoms significantly improves the hydrogen evolution performance of the CdS quantum dot photocatalyst; from the data comparison between Example 1 and Comparative Example 2 in Table 2, it can be seen that not all rare earth metal doping can achieve good results. If the rare earth metal does not contain Sm or Ce, its hydrogen evolution performance is even worse than that without doping; from the data comparison between Example 1 and Comparative Example 3 in Table 2, it can be seen that the pH in the preparation process has a crucial influence on the experimental results. If the preparation is carried out in an acidic solution, the performance of the catalyst will deteriorate sharply.
[0223] From the data comparison of Examples 1-21 and Examples 25-27 in Table 2, it can be seen that different types of metal single atoms and / or metal single atom doping amounts have different effects on improving the photocatalytic performance of CdS quantum dots, among which Bi and Sm have the best effects. However, changing the doping amount, especially when the doping amount of Bi single atoms is higher than the range of 0.03wt% to 1.5wt%, will cause the catalyst performance to decrease.
[0224] From the data comparison of Example 1 and Examples 22-24 in Table 2, it can be seen that changing the molar ratio of the cadmium source and the sulfur source, the reaction temperature and / or time will also affect the hydrogen evolution performance of the catalyst. The molar ratio of the cadmium source and the sulfur source is controlled within the range of (0.9-1.1):(0.9-1.1), the reaction temperature is controlled within the range of 115°C-125°C, and the reaction time is controlled within the range of 30min-75min, which can make the catalyst show better hydrogen evolution performance.
[0225] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A photocatalyst, characterized in that: The photocatalyst includes CdS quantum dots and metal single atoms doped in the CdS quantum dots; The metal single atom includes any one of a transition metal, a rare earth metal or Bi, and the rare earth metal includes Sm or Ce.
2. The photocatalyst according to claim 1, characterized in that The metal single atom comprises Sm or Bi; Preferably, the transition metal includes any one of Ni, Mo or Nb; Preferably, when the metal single atom includes a transition metal or a rare earth metal, the mass ratio of the CdS quantum dots to the metal single atom is 100:(0.01-3); Preferably, when the metal single atom includes Bi, the mass ratio of the CdS quantum dots to the metal single atom is 100:(0.03-1.5); Preferably, the average particle size of the CdS quantum dots is 2nm to 3nm; Preferably, the structure of the CdS quantum dots includes a cubic zinc blende structure.
3. A method for preparing a photocatalyst as claimed in claim 1 or 2, characterized in that: The preparation method comprises: (1) first mixing a cadmium source, a doping metal source solution, a thiol compound and a solvent, and adjusting the pH to ≥ 10 using a pH adjuster to obtain a Cd precursor solution; (2) performing a second mixing of the Cd precursor solution and a sulfur source, and reacting the mixture under heating conditions to obtain the photocatalyst; The doping metal source in the doping metal source solution includes any one of a transition metal source, a rare earth metal source or a Bi source, and the rare earth metal source includes a Sm source or a Ce source.
4. The method for preparing a photocatalyst according to claim 3, characterized in that: The transition metal source includes any one of a Ni source, a Mo source or a Nb source; Preferably, the doping metal source comprises a Sm source or a Bi source; Preferably, the concentration of the doping metal source solution is 0.005 mol / L to 0.02 mol / L; Preferably, when the doping metal source includes a transition metal source or a rare earth metal source, the mass ratio of the sum of the mass of the cadmium in the cadmium source and the mass of the sulfur in the sulfur source to the mass of the doping metal in the doping metal source is 100:(0.01-3); Preferably, when the doping metal source includes a Bi source, the mass ratio of the sum of the mass of cadmium in the cadmium source and the mass of sulfur in the sulfur source to the mass of the doping metal in the doping metal source is 100:(0.03-1.5); Preferably, the molar ratio of the cadmium source to the mercapto compound is (50-70):
1.
5. The method for preparing a photocatalyst according to claim 3 or 4, characterized in that: The pH adjuster includes NaOH solution; Preferably, the mass fraction of NaOH in the NaOH solution is 20% to 40%; Preferably, the first mixing is performed under stirring.
6. The method for preparing a photocatalyst according to any one of claims 3 to 5, characterized in that: The sulfur source includes sodium sulfide; Preferably, the molar ratio of the cadmium source to the sulfur source is (0.9-1.1):(0.9-1.1).
7. The method for preparing a photocatalyst according to any one of claims 3 to 6, characterized in that: Step (2) is carried out in an inert gas atmosphere; Preferably, the reaction in step (2) is carried out under stirring; Preferably, the reaction temperature in step (2) is 115°C to 125°C; Preferably, the reaction time in step (2) is 30 min to 75 min.
8. The method for preparing a photocatalyst according to any one of claims 3 to 7, characterized in that: The product after the reaction in step (2) is sequentially washed and dried; Preferably, the washing method comprises washing multiple times in a mixed solution of secondary water and ethanol; Preferably, the drying temperature is 70°C to 90°C; Preferably, the drying time is 5 h to 7 h.
9. The method for preparing a photocatalyst according to claim 3, characterized in that: The preparation method comprises the following steps: (1) preparing a doping metal source solution with a concentration of 0.005 mol / L to 0.02 mol / L, and mixing the prepared doping metal source solution, the cadmium source, the thiol compound and the solvent in a molar ratio of 50 to 70:1 under stirring, and then adjusting the pH to ≥ 10 using a NaOH solution with a NaOH mass fraction of 20% to 40% to obtain a Cd precursor solution; (2) in an inert gas atmosphere and under stirring conditions, the Cd precursor solution and the sulfur source are mixed for a second time according to a molar ratio of cadmium source to sulfur source (0.9-1.1):(0.9-1.1), reacted at 115° C. to 125° C. for 30 min to 75 min, the reaction product is washed multiple times in a mixed solution of secondary water and ethanol, and dried at 70° C. to 90° C. for 5 h to 7 h to obtain the photocatalyst; the doped metal source includes a Sm source or a Bi source; When the doping metal source includes an Sm source, the mass ratio of the sum of the mass of cadmium in the cadmium source and the sulfur in the sulfur source to the doping metal in the doping metal source is 100:(0.01~3); when the doping metal source includes a Bi source, the mass ratio of the sum of the mass of cadmium in the cadmium source and the sulfur in the sulfur source to the doping metal in the doping metal source is 100:(0.03~1.5).
10. Use of the photocatalyst as claimed in claim 1 or 2 in the degradation of plastic waste.
Citation Information
Patent Citations
Preparation and application of metal ion doped CdSe quantum dot photocatalyst
CN103736504A
Method for preparing Bi-doped ZnS photocatalyst by taking ionic liquid as template
CN104667949A
Doped quantum dot catalyst, preparation method thereof, hydrogen production system comprising doped quantum dot catalyst, and hydrogen production method
CN105478148A
Ni-doped CdS complex photocatalyst and preparation method and application thereof
CN110586189A
Photocatalyst and photocatalytic methods
WO2018096103A1
Cited By
Preparation method of quantum dot homogeneous photocatalytic material and application of quantum dot homogeneous photocatalytic material in preparation of methanol by photocatalysis of methane
CN121372520A
Preparation method of quantum dot homogeneous photocatalytic material and application of quantum dot homogeneous photocatalytic material in photocatalytic methane to methanol
CN121372520B